Neuronal Nitric Oxide Synthase Contributes to PTZ Kindling-Induced Cognitive Impairment and Depressive-Like Behavior - Zhu, Xinjian; Dong, Jingde; Han, Bing; Huang, Rongrong; Zhang, Aifeng; Xia, Zhengrong; Chang, Huanhuan; Chao, Jie; Yao, Honghong (Frontiers in Behavioral Neuroscience, 2017)
Epilepsy is a chronic neurological disease which is usually associated with psychiatric comorbidities. Depression and cognition impairment are considered to be the most common psychiatric comorbidities in epilepsy patients. However, the specific contribution of epilepsy made to these psychiatric comorbidities remains largely unknown. Here we use pentylenetetrazole (PTZ) kindling, a chronic epilepsy model, to identify neuronal nitric oxide synthase (nNOS) as a signaling molecule triggering PTZ kindling-induced cognitive impairment and depressive-like behavior. Furthermore, we identified that both hippocampal MAPK and PI3K/AKT signaling pathways were activated in response to PTZ kindling, and the increased MAPK and PI3K/AKT signaling activation was paralleled by increased level of reactive oxygen species (ROS) in the hippocampus. However, the PTZ kindling-induced MAPK, PI3K/AKT signaling activities and the ROS level were attenuated by nNOS gene deficiency, suggesting that nNOS may act through ROS-mediated MAPK and PI3K/AKT signaling pathways to trigger cognition deficit and depressive-like behavior in PTZ-kindled mice. Our findings thus define a specific mechanism for chronic epilepsy-induced cognitive impairment and depressive-like behavior, and identify a potential therapeutic target for psychiatric comorbidities in chronic epilepsy patients.